Dramatic Technique in Frost’s Poetry - Gurung, Gol Man (Interdisciplinary Journal of Management and Social Sciences, 2021)
Robert Frost’s poetry is consolidation of theme, content, form, technique, and prosody. When words are forced into a strict prosody without apprehension of connotation, they become forced obstinate and merely clinking sounds. The combination of form, content, and music generate beauty in verse. By means of the use of dialogue and monologue, he gives genuine treatment to realistic situation in his poems. Three poems: "The Death of the Hired Man", "Stopping by Woods on a Snowy Evening" and "West Running Brook" present brilliance, vivacity, and a sense of exhilaration due to the dramatic techniques of presentation. The speaker in these poems should not be taken literally to represent Frost, rather a character who replies in typical ways to the world around him. The speaker is independent, lonely, and sensitive and he often yearns for acquaintance. The magnitude of his verse lies in its handling of man in relation to nature through dramatic technique.